Role of research in community arts: Developing an evaluation framework in Singapore. Issue 5 (19th October 2016) - Cho, Im Sik; Duong, Quyen; Nasution, Ivan
Abstract: Community arts in Singapore have gradually evolved since the country became a self-governing state in 1959, from a mostly top–down approach of government-initiated programs to include more ground-up initiatives. This shift advocated embracing community members not only as audience but also as originators, through community-focused policies and programs aimed at making arts and culture more accessible. In this changing context, this article seeks to understand the relationship between cultural research and practice, and examines a collaborative project between the National Arts Council of Singapore and the National University of Singapore that aims to create a community-based evaluation framework to assess and evaluate arts and culture-focused community spaces in Singapore. Results from the study show that research can inform change that not only facilitates collaboration among different stakeholders in the process of creating the outcome, but also promotes further ground-up engagement in community arts by empowering practitioners with an evaluation framework.